Understanding underrecovery, overtraining and burnout in the developing athlete - Pelka, M.; Kellmann, M. (Routledge handbook of talent identification and development in sport, 2017)
Seeking elite Status as a youth athlete and competing at elite levels require athletes to invest a large amount of time and intense effort in training (Gustafsson, Davis, Skoog, Kenttä, & Haberl, 2015). Young athletes have to dedicate significant resources to deliberate practice and maintain this level of dedication over several years in order to achieve their goals (Ward, Hodges, Starkes, & Wilhams, 2007). This is a challenging endeavour and the experience of aspiring athletes who undertake it can differ considerably. For some athletes, this process can be psychologically rewarding and place them on a path to long-term sport participation (Jowett, Hill, Hall, & Curran, 2016). For others, the psychological and physical demands can prove too great, fostering an experience laden with self-doubt and frustration that places them on a path to extreme disaffection (Jowett et al., 2016). That might lead to detrimental consequences such as underrecovery, overtraining, injuries, and burnout (Gustafsson, Hassmen, Kenttä, & Johansson, 2008) and more severe mental health problems (Hughes & Leavey, 2012). Curran, Appleton, Hill, and Hall (2013) indicated that aspiring young athletes may be at particular risk. This risk increases when elite athletes are injured, face career termination, or experience performance difficulties (Rice et al., 2016). As a result, in many sports, negative consequences such as burnout and subsequent dropout are a common occurrence (Crane & Temple, 2015; Dubuc, Schinke, Eys, Battochio, & Zaichowsky, 2010; Cresswell & Eklund, 2007; Harris & Watson, 2014; Strachan, Cote, & Deakin, 2009).